Aset Budaya Sebagai Konsep Destination Branding Desa Ngadas Kabupaten Malang - Dhika Yuan Yurisma (LPPM Institut Bisnis dan Teknologi Indonesia, 2021)
Destination branding is an effort to build people's perceptions of a destination, by marketing or introducing existing potentials and advantages, so that it can become an identity for a destination. Ngadas Village, located in Malang Regency, is one of the four villages of the Tengger tribe that has cultural potential and natural wealth that can be developed into a tourist destination. Therefore, it is necessary to design a destination branding for Ngadas Village so that its potential can be recognized and become a characteristic of the village. The main purpose of this design is to communicate Ngadas Village to the wider community so that the cultural heritage of Ngadas Village can be maintained and sustainable, besides that it can also help the welfare of the people of Ngadas Village. With this Destination branding, Ngadas village has the opportunity to introduce its potential, while preserving the cultural heritage for its successors. The research method used in Destination branding uses qualitative methods with a direct approach to the field and in-depth interviews with related parties to deepen knowledge about Ngadas village. From this method, it is found that the Ngadas village has cultural assets that become verbal concepts, visual concepts and media strategies in this design.